2016
DOI: 10.4012/dmj.2015-390
|View full text |Cite
|
Sign up to set email alerts
|

Diametral tensile strength of novel fast-setting calcium silicate cement

Abstract: Novel fast-setting calcium silicate cement with fluoride (CSC) has been developed for potential applications in tooth crown. The aim of this study was to test the diametral tensile strength (DTS) of different CSC compositions in humid condition on day1, 28, and 180. We tested 'bond CSC' with 3.5% fluoride and no radiocontrast, 'CSC' with 3.5% fluoride and 10% radiocontrast, 'ultrafast CSC' with 3.5% fluoride and 20% radiocontrast, 'high fluoride CSC' with 15% fluoride and 25% radiocontrast, Biodentine, and MTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 32 publications
2
31
0
3
Order By: Relevance
“…The second part of this study investigated the effect of phytic acid on diametral tensile strength because attempts to shorten setting time should not alter the physical properties of the biomaterial. The diametral tensile strength test is an accepted and commonly used method to measure the tensile strength of dental materials and is used to analyse the changes in the mechanical properties of brittle materials, such as calcium silicate-based cements, after mixing with different chemicals (28,29). Similar to that in a previous work (28), in this work, Biodentine ® presented higher diametral tensile strength than MTA.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The second part of this study investigated the effect of phytic acid on diametral tensile strength because attempts to shorten setting time should not alter the physical properties of the biomaterial. The diametral tensile strength test is an accepted and commonly used method to measure the tensile strength of dental materials and is used to analyse the changes in the mechanical properties of brittle materials, such as calcium silicate-based cements, after mixing with different chemicals (28,29). Similar to that in a previous work (28), in this work, Biodentine ® presented higher diametral tensile strength than MTA.…”
Section: Discussionsupporting
confidence: 70%
“…The diametral tensile strength test is an accepted and commonly used method to measure the tensile strength of dental materials and is used to analyse the changes in the mechanical properties of brittle materials, such as calcium silicate-based cements, after mixing with different chemicals (28,29). The diametral tensile strength test is an accepted and commonly used method to measure the tensile strength of dental materials and is used to analyse the changes in the mechanical properties of brittle materials, such as calcium silicate-based cements, after mixing with different chemicals (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear regression model suggested a bond‐strength increase as a function of time only for Protooth; no such increase was observed for the other materials tested. Previously, we observed that Protooth cement possessed improved diametral tensile strength in comparison with ProRoot MTA . Improved tensile strength or mechanical properties may explain the better bonding ability of the new cement.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the fast setting time, improved mechanical properties , apatite‐forming or mineralizing ability , biocompatibility , acceptable clinical results , interfacial gap closure capability , and superior long‐term bonding to dentine, as observed in this study, support further testing on Protooth for potential applications in the tooth crown. Accordingly, Protooth may be a candidate for pulp protection, treatment of endodontic complications, caries sealing, and post or crown cementation.…”
Section: Discussionmentioning
confidence: 99%